Protein content of grains of different size fractions in malting barley - Magliano, Patricio Nicolás (2014)
The negative relationship between grain size (percentage >2.5mm) and protein content usually observed in barley grain samples is attributed to the presence of thin grains. The objective of this study was to determine whether, in grain samples from a given environment, thin grains had a different protein content than plump grains. Grain samples from field experiments were analysed for grain yield, size and protein content of the whole sample and of four size fractions within each sample. Grain yield ranged from 1.5 to 6.5mgha1 and grain protein (whole sample) ranged from 6.8 to 13.4 %. Most of the variation observed in protein content was explained by the ratio of nitrogen availability to grain yield. Within a grain sample, thin grains had more protein than plump grains (>2.5mm) only when the protein content of the whole sample was high, that is, when the grain sample came from an environment with a high relative abundance of nitrogen. The fact that grain samples with low grain size tend to have high protein content is not due to the presence of a high proportion of thin grains, because thin grains do not always have more protein than plump grains.